Socio-cultural factors affecting breastfeeding in Northern Mexico: insufficiency and dissatisfaction - Diana Bueno-Gutiérrez; Fernanda Tejeda-López; Ana Lilia Armendariz-Anguiano; Glenda Díaz-Ramírez; Ileana De Anda-Duran (Discover Public Health)
Abstract Background The prevalence of 33.6% Exclusive Breastfeeding (EBF) infants under six months of age in Mexico is far from the World Nutrition Assembly goal. To improve those rates, we must have a better understanding of the obstacles influencing breastfeeding in a specific context. Objectives The primary objective was to evaluate the association between breastfeeding obstacles and infant feeding practices (IFP) in mother/infant dyads attending health care services. Methods This was a cross-sectional study that included mothers of infants less than 4 months of age attending primary health care centers in Tijuana, Mexico. Breastfeeding obstacles were assessed with a questionnaire developed from previous research that used a socio-ecological model. Infant feeding practices were evaluated with a 24 h recall method. Regression models were applied to determine the associations between breastfeeding obstacles and IFP. Results A total of 447 mother/infant dyads were included. Mothers had a mean age of 26.6 years and infants had a mean age of 1.8 months. Significant associations were found between all IFP and two obstacles: Perception of Insufficient Milk (PIM) and infant dissatisfaction. Women were less likely to EBF when they reported PIM (OR 0.21; 95% CI 0.14, 0.32), and infant dissatisfaction (OR 0.17; 95% CI 0.11, 0.26). Conclusions Our findings suggest that mothers who experience PIM and infant dissatisfaction may be at risk of lower breastfeeding and higher formula use in this context. Since IFP depend on the socio-cultural environment in which the mother lives, identification of obstacles in particular settings are necessary to support breastfeeding.